The occurrence of Sphaerospora renicola K-stages in the choroidal rete mirabile of the common carp - Molnár, K (Folia parasitologica, 1993)
It is known from earlier studies that the so-called K-protozoa, the late presporogonic stages of Sphaerospora renicola, a parasite causing renal sphaerosporosis in common carp (Cyprinus carpio), accumulate in the swimbladder wall and give rise to the disease called myxosporean swimbladder inflammation. The present study indicates that in the case of intensive infection these parasites also occur in the rete mirabile of the choroid of the eye, causing haemorrhages and necrosis. The results suggest that the K-stages of S. renicola are located in the blood path just like the early presporogonic C-stages; however, as they get stuck in organs rich in capillaries, it is difficult to demonstrate them from the blood of the common carp.
Keywords: choroidea; Fish Diseases; Capillaries; Inflammation; Air Sacs; Protozoan Infections; Eukaryota; kapři; choroidální krvácení; nekróza; protozoální infekce zvířat; zánět; vzdušné vaky; Animals; Necrosis; Protozoan Infections, Animal; zvířata; nemoci ryb; Carps; kapiláry; protozoální infekce; Choroid Hemorrhage; Choroid